2021
DOI: 10.3389/fonc.2021.616390
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: MiR-365a-3p-Mediated Regulation of HELLS/GLUT1 Axis Suppresses Aerobic Glycolysis and Gastric Cancer Growth

Abstract: Gastric cancer (GC) is a common and invasive malignancy, which lacks effective treatment and is the third main reason of cancer death. Metabolic reprogramming is one of the main reasons that GC is difficult to treat in various environments. Particularly, abnormal glycolytic activity is the most common way of metabolism reprogramming in cancer cells. Numerous studies have shown that microRNAs play important roles in reprogramming glucose metabolism. Here, we found a microRNA-miR-365a-3p, was significantly downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…addition, high levels of LSH correlates with a poor prognosis in gastric cancer [72]. The mechanism associated with this observation might act through reduced levels of miR-365a-3p, since this microRNA binds to its 3' untranslated region (UTR) of the HELLS transcript and represses its translation, thereby resulting in reduced LSH levels and enhanced carcinogenesis [73].…”
Section: Lsh Is a Bridge Regulator In Oncogenesismentioning
confidence: 99%
“…addition, high levels of LSH correlates with a poor prognosis in gastric cancer [72]. The mechanism associated with this observation might act through reduced levels of miR-365a-3p, since this microRNA binds to its 3' untranslated region (UTR) of the HELLS transcript and represses its translation, thereby resulting in reduced LSH levels and enhanced carcinogenesis [73].…”
Section: Lsh Is a Bridge Regulator In Oncogenesismentioning
confidence: 99%
“…Previous bioinformatic studies have identified amounts of GC related miRNAs (3,(5)(6)(7)(8). Some circulating serum exosomal miRNAs were proposed as novel biomarkers for GC diagnosis, such as miR-92a-3p, miR-500a-3p, miR-1246, and miR-423-5p (3,5,(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that miR-365a-3p acts as a cancer suppressor gene in various cancers [22,38,39]. Therefore, we investigated whether miR-365a-3p inhibits OS growth.…”
Section: Mir-365a-3p Targeted Pgk1 Directly In Os Cells and Inhibited Os Growthmentioning
confidence: 99%